Slut shaming ou exposição íntima online: violência contra a mulher e políticas públicas de enfrentamento - Sousa, Letícia de Mélo (2021)
The online intimate exposure (revenge porn; slut shaming) refers to the culture of humiliation of women for their sexual practices, updated through the internet, with the purpose of control and domination, through victim blaming. The aim of this research is to analyze the experience of intimate online exposure experienced by women and the confrontation of this violence by public policies. Three studies were carried out, based on the gender perspective: the first, documentary, by searching 55 official documents, national and international, about public policies focused on combating violence against women; the second study started from an online questionnaire on the experience and understanding of Brazilian women regarding violence, with 1.028 participants; the third study was conducted through six individual semi-structured interviews with professionals from the public policy of combating violence against women. Quantitative data were analyzed using descriptive statistics (SPSS 20) and qualitative data through thematic-categorical content analysis (MaxQDA). The results show that Brazil has legal mechanisms to guarantee the rights of women victims of online intimate exposure. It was found that 5% had undergone online intimate exposure, however, the search for defense or service policies was low. The interviewed professionals affirmed that the naturalization of psychological violence and the victim blaming in intimate exposure online are the main challenges to their attendance in public policies. We estimate that this research will contribute to construction of scientific knowledge about this form of violence, and thus can base the professional care to victims and actions of confront.